2003
DOI: 10.1115/1.1536654
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Distribution of Cell Death and Matrix Damage in Impacted Chondral Explants Varies with the Presence of Underlying Bone

Abstract: Excessive mechanical loading can lead to matrix damage and chondrocyte death in articular cartilage. Previous studies on chondral and osteochondral explants have not clearly distinguished to what extent the degree and the distribution of cell death are dependent on the presence of an underlying layer of bone. The current study hypothesized that the presence of underlying bone would decrease the amount of matrix damage and cell death. Chondral and osteochondral explants were loaded to 30 MPa at a high rate of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Finally, several in vivo animal studies have confirmed that trauma-induced chondrocyte death is followed by progressive degenerative joint changes (Radin et al 1973;Ewers et al 2001;Krueger et al 2003;. Thus, preservation of cell viability in articular cartilage after mechanical damage is important for matrix integrity and tissue healing, and ultimately in the prevention of OA.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, several in vivo animal studies have confirmed that trauma-induced chondrocyte death is followed by progressive degenerative joint changes (Radin et al 1973;Ewers et al 2001;Krueger et al 2003;. Thus, preservation of cell viability in articular cartilage after mechanical damage is important for matrix integrity and tissue healing, and ultimately in the prevention of OA.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators have failed to demonstrate such changes in MMP expression, but have reported a reduction in type II collagen mRNA upon cyclical loading (13). Cell death, by apoptosis and necrosis, is increased in cartilage explants subjected to high static loads, especially in the superficial zone (14)(15)(16), although loading the tissue still attached to bone causes less cell death (17).…”
Section: S-met/cys Into Proteins Secreted By Cartilage Explants or Bymentioning
confidence: 99%
“…Recent studies have reported that static and cyclic compressive loading of varying magnitudes, as well as blunt impacts, result in increased cell death in articular cartilage (Chen et al 1999(Chen et al , 2003Torzilli et al 1999;Ewers et al 2001;Quinn et al 2001;Lucchinetti et al 2002;Krueger et al 2003). Examination of the distribution of cell death has been shown to be preferentially concentrated in the superficial tangential zone (STZ) after cyclic loading at moderate magnitudes (peak stress of 1 MPa) (Lucchinetti et al 2002;Chen et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…e Schematic of samples tested in the microscopy device shown in d the relationship between the depth-dependent strain and cell death on the same tissue type or under the same loading configuration. Moreover, injury studies have generally examined the behavior of cell death under impact and/or cyclic loading with load control that results in large compressive strain magnitude, typically up to 50-60% strain (Ewers et al 2001;Flachsmann et al 2001;Krueger et al 2003), whereas the literature studies on the depth-dependent mechanical properties of cartilage have generally been tested under a smaller strain range, typically 20-30% strain.…”
Section: Introductionmentioning
confidence: 99%